IMPACT OF DIGITAL TECHNOLOGIES ON THE EDUCATION SYSTEM - Tojiboyeva Shahrizoda (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This article examines the multifaceted impact of digital technologies on modern education. As artificial intelligence, e-learning platforms, and interactive digital tools are increasingly integrated into the educational environment, it is crucial to understand their pedagogical relevance. The study draws on recent academic literature and empirical observations to analyze how digital transformation impacts teaching quality, student engagement, and learning outcomes. The study findings suggest that while digital technologies offer significant advantages in terms of accessibility, personalization, and efficiency, their effective implementation requires adequate infrastructure, teacher training, and institutional support. The article concludes with recommendations for educators, policymakers, and technology developers seeking to harness the full potential of digital innovations in education.